One country, many religions: Muslim/Christian relations in Nigeria and the modern secular state (2013)
Questions such as will Nigeria remain one country and why do Muslims seek to use the Shari’ah to divide the country have taken up a sense of urgency with the acts of terrorism coloring Islam and Muslims. To answer these questions, this paper explores the history of Muslim/Christian relations in Nigeria. It also examines the question that divides Nigerians, especially Muslim and Christians most-the relation between religion and politics. The historical approach has been adoption to underscore the historicity of Muslim/Christian relations in Nigeria. For Christians, Nigeria is a secular state while for Muslims; Islam is "the lodestar" of politics. For Nigeria to remain one country, this paper proposes the model of a commonwealth of Religions that eschews the extremes of both the modem secular and classical Islamic states by fusing politics not with Islam, but with religions. This is because both states suppress the religious identities, markers and symbols of the other. They both make the other assimilate either the dominant secular norm of Christianity or the Islamic ethos. Therefore, instead of "oneness amidst the manyness" of religions and "combinations among all religious peoples," this paper calls for the creation of the Commonwealth of all Religions in the country.